Analysis of Microwave Absorption Properties of Graphene Oxide from Rice Husk Waste - Andari Oktafiani; Ramli Ramli; Yenni Darvina; Gusnedi Gusnedi (Department of Physics – Universitas Negeri Padang UNP, 2023)
Graphene Oxide (GO) was synthesized with variations in carbonization temperatures of 250 °C, 300 °C, and 350 °C using the modified Hummers method. The results of the synthesis of GO will then be tested for microwave absorbing properties because it can be applied in various fields, such as information technology, medical equipment, industry, polymer synthesis, and organic synthesis. Therefore, in this report, GO uses rice husk waste instead of graphite as a carbon source because rice husk waste is abundant in nature and easy to obtain than graphite. In addition to reducing waste in Indonesia, this study aimed to determine the crystal size and GO functional groups and analyze the properties of microwave absorbers. X-ray diffraction (XRD) was used to determine the crystal size. The GO functional groups were determined using Fourier Transform Infrared (FTIR), and the microwave absorption characteristics of GO were analyzed using a Vector Network Analyzer (VNA). The XRD results show GO peaks between 26° peaks and 44° peaks. In the FTIR results, there are a collection of GO practices, in particular CO, C = C, and C = O. In the VNA results, the best microwave absorption properties are at an ignition temperature of 350 °C with the lowest reflection value - 39.95 dB, the highest absorption coefficient is 99%, and the absorption bandwidth is 0.06 GHz at a frequency of 8.5 GHz